AKUNTANSI SUMBER DAYA MANUSIA SEBAGAI ALTERNATIF DALAM PENYUSUNAN LAPORAN KEUANGAN - -, Suwarto - (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2006)
ABSTRACT Conventional accounting journal human resource us expenses not as assets. While human resource accounting journal human resource as assets in order to appraisal it’s monetary value. Present and tomorrow, potential of human resource can give advantages at business. At tomorrow, it’s advantages will give economy value for enterprise in planning and give economy value for enterprise in planning and control human resource. Keywords: Accounting human resource, expense, assets advantage.